X-Ray Diffraction anaylsis of sediment core PS115/2_2 - Ruediger Stein; Thomas Frederichs; Kirsten Fahl; Walter Geibert; Jens Matthiessen; Frank Niessen; Christoph Vogt; Cynthia Sassenroth; Evgenia A Bazhenova (PANGAEA, 2025)
Sediment Core PS115/2-2 was recovered from the Amundsen Basin in 3600 m water depth at the eastern flank of the Gakkel Ridge during Polarstern Expedition PS115/2 in 2018 (Stein, 2019). The well-dated core is used to reconstruct in detail the interrelationship between ice-sheet dynamics and organic carbon burial in the central Eurasian Basin during the last 430 kyr, and to correlate marine and terrestrial records of the Eurasian Ice Sheet (EIS) history. Due to the complex geology of the circum-Arctic Ocean hinterland, specific mineral assemblages determined in sediment cores from the eastern Eurasian Basin may give information about the detrital sediment provenance, transport processes and EIS history (cf., Stein et al., 1994; Vogt, 1997; Wahsner et al., 1999; Stein, 2008). In this context, X-Ray diffraction (XRD) analyses were carried-out using ground bulk sediment. The relative contents of the determined minerals are expressed as ratio of the XRD single mineral peak intensity vs. sum of total analyzed intensities (Vogt, 2009). For details and methods, we refer to Stein et al. (this paper).
In: Stein, R et al. (2025): A 430 kyr multi-proxy record of Eurasian Ice Sheet history and organic carbon burial in the eastern Eurasian Basin, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.975790